Arterial stiffness, vascular calcification and osteoporosis — common mechanisms of interaction (literature review) - O.I. Nishkumay; H.V. Mostbauer; O.O. Alekseenko; K.I. Moskalenko; P.O. Lazarev; M.I. Shevchuk (Bolʹ, Sustavy, Pozvonočnik, 2022)
Introduction. The problem of cardiovascular morbidity and mortality remains an urgent issue of modern medicine, and arterial stiffness is its independent predictor. Lively discussions about the correct approach to the prevention and treatment of comorbid conditions – increased vascular stiffness as an influential factor of the cardiovascular events and decreased bone mineral density (osteoporosis), primarily arise against the background of the need and safety of calcium and vitamin D supplements. The purpose was to search for literature data as for possible common pathogenetic links in the progression of arterial stiffness and the development of osteoporosis in order to assess the safety of the use of drugs to prevent osteoporotic fractures. Results. Analysis of literature sourses had showed that possible osteogenic factors affecting arterial stiffness may be: secondary hyperparathyroidism, disbalance of the RANK/RANKL/OPG system, inhibition of vitamin K-dependent matrix proteins (Gla-protein), osteopontin, etc. Conclusions. Today, there are many hypotheses confirming the possible influence of osteogenic factors on vascular stiffness and arterial calcification. Therefore, the search for sensitive markers and the development of screening protocols for the patients with risk factors for both osteoporosis and vascular changes are extremely relevant. A special issue is the possibility of using monotherapy for these comorbid pathologies, which can safely and efficiently influence the prevention of complications – both low-energy osteoporotic fractures and cardiovascular catastrophes. This will be the focus of our further research.